2021
DOI: 10.1186/s12916-020-01873-7
|View full text |Cite|
|
Sign up to set email alerts
|

Non-genetic risk and protective factors and biomarkers for neurological disorders: a meta-umbrella systematic review of umbrella reviews

Abstract: Background The etiologies of chronic neurological diseases, which heavily contribute to global disease burden, remain far from elucidated. Despite available umbrella reviews on single contributing factors or diseases, no study has systematically captured non-purely genetic risk and/or protective factors for chronic neurological diseases. Methods We performed a systematic analysis of umbrella reviews (meta-umbrella) published until September 20th, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 221 publications
(334 reference statements)
0
32
0
Order By: Relevance
“…Studies excluded were: a) systematic reviews or meta-analyses other than umbrella reviews, individual studies (including Mendelian randomization studies and randomized controlled trials), clinical cases, conference proceedings, and study protocols; b) umbrella reviews not reporting quantitative data; c) umbrella reviews addressing outcomes other than the onset of an established mental disorder (e.g., those related to clinical outcomes such as relapse, remission or treatment response 15,23 , or biomarkers); d) umbrella reviews employing other classification approaches, such as GRADE 25 , because these mostly apply to interventional effects, not aetiology 26 .…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Studies excluded were: a) systematic reviews or meta-analyses other than umbrella reviews, individual studies (including Mendelian randomization studies and randomized controlled trials), clinical cases, conference proceedings, and study protocols; b) umbrella reviews not reporting quantitative data; c) umbrella reviews addressing outcomes other than the onset of an established mental disorder (e.g., those related to clinical outcomes such as relapse, remission or treatment response 15,23 , or biomarkers); d) umbrella reviews employing other classification approaches, such as GRADE 25 , because these mostly apply to interventional effects, not aetiology 26 .…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…We present here the first systematic synthesis of umbrella reviews of non‐purely genetic risk and protective factors for mental disorders. This approach has been termed “meta‐umbrella” and offers an overarching field‐wide overview to comprehensively assess a certain topic 23 . Our aims were to provide an evidence‐synthesis comparative atlas of the consistency and magnitude of risk and protective factors for mental disorders beyond genetics, and to formulate recommendations for the next generation of aetiopathological research and preventive psychiatry.…”
mentioning
confidence: 99%
“…While the T allele is a ”risk allele” for neurodegeneration, it may also be a ”risk allele” for smoking, at least in healthy individuals. Given that smoking increases dementia risk [ 98 ], BDNF rs56164415 polymorphism may have moderating or additive effects, which deserves future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the internalization of UA crystals by leukocytes leads to production of free radicals, release of cathepsin B and activation of inflammasome (37,38). Interestingly, higher SUA levels have been hypothesized to play a protective role in the development of some neurological disorders such as dementia, multiple sclerosis, Alzheimer's disease and Parkinson's disease (39)(40)(41)(42). In a recent metaanalysis involving 5,575 participants, Zhou et al demonstrated a significant inverse association between SUA and Alzheimer's disease or Parkinson's disease (43).…”
Section: Uric Acid As Protective Factormentioning
confidence: 99%